Congenital absence of the gallbladder in a child: a case report - Wei, Xiao; You, Liying; Liu, Chun; Xu, Xu (Frontiers in Pediatrics, 2024)
Background: Congenital absence of the gallbladder (CAGB) is an exceedingly rare embryological anomaly of the biliary system, with a complex etiology involving the failure of gallbladder formation during embryogenesis. Clinical manifestations are diverse; most patients are asymptomatic, while some present with symptoms such as biliary colic. The complexity of its clinical presentation and radiological features renders diagnosis challenging.Presentation: Fetal ultrasound at 22 weeks of gestation revealed an absent gallbladder. At 9 years and 11 months of age, the child exhibited significant weight gain and abnormalities. Abdominal ultrasound and magnetic resonance images demonstrated fatty liver and gallbladder agenesis. Liver function tests indicated mild abnormalities, with aspartate aminotransferase at 67 IU/L and alanine aminotransferase at 44 IU/L. Following 6 months of hepatoprotective and lipid-lowering therapy, a satisfactory treatment response was achieved, with normalization of liver function and improvement in fatty liver. Conclusions: CAGB may be associated with other congenital abnormalities, although isolated cases are uncommon. Clinically, it may manifest as nonspecific biliary, gastrointestinal, or urinary symptoms, mimicking various digestive disorders and leading to misdiagnosis. Genetic sequencing and in-depth embryological research may elucidate the etiology and enhance diagnostic accuracy.